PENERJEMAHAN KOSA KATA BUDAYA DALAM SENYUM KARYAMIN DAN KARYAMIN’S SMILE - Evi Melila Sari (Kantor Bahasa Kalimantan Timur, 2017)
Translation is the process of transfering meaning from source language to target language . The purpose of this paper is to find out the category of cultural words in the novel Senyum Karyamin which is translated into Karyamin’s Smile and uncover translation procedures used in translating those words . This paper is qualitative descriptive . The result shows four cultural words in ecological subcategory, a cultural word in material culture subcategory, and three cultural words in the organizational subcategory . Translation strategies mostly used are loanwords with explanation and without explanation.